Accelerated formation of methane hydrates in the porous SiC foam ceramic packed reactor. (1st December 2019) - Liu, Xiaowan; Tian, Linqing; Chen, Daoyi; Wu, Guozhong
Graphical abstract: Highlights: CH4 hydrate induction time decreased by up to 88% using SFC packings. CH4 hydrate growth rate increased by up to 95% using SFC packings. Water conversion rate to hydrate increased by up to 1.2-fold using SFC packings. A small particle size and large pore size of SFC is favorable for hydrate formation. SFC packings have high reusability without obviously losing performance. Abstract: A new approach was proposed to facilitate methane hydrate formation using the porous SiC foam ceramic (SFC) packings without the assistance of mechanical agitation. The performance of regular packings with two different stacking patterns (parallel stacking and perpendicular stacking) and random packings with six different structure parameters (particles size: 3 – 9 mm, pore size: 0.5 – 1.0 mm) were tested. The overall results clearly demonstrated the promotion effects of SFC packings on the kinetics of hydrate formation, which also increased the repeatability of hydrate synthesis especially under low driving force. Compared with the control experiments, the induction time was decreased by up to 88%, the maximum growth rate was increased by up to 95%, while the degree of water conversion to hydrates was increased by up to 1.2-fold (274.6 K, 7.3 MPa). Insignificant decrease was observed in the above performance during the five cycles of cooling-melting experiments, indicating the good reusability of the SFC packings. To the best of our knowledge, the porous SFC materials were for the first time successfully employed for accelerating gas hydrate formation, which provided an alternative method to improve the efficiency of the natural gas storage.